The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1542/peds.2011-2657
|View full text |Cite
|
Sign up to set email alerts
|

Parental Separation and Pediatric Cancer: A Danish Cohort Study

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Cancer in a child may affect the quality of the parents' relationship, but few studies have examined a potential effect on parental divorce, and no studies have accounted for the proportion of couples that live outside formal marriages. WHAT THIS STUDY ADDS:In this nationwide registry-based study with up to 20 years of follow-up, we included both married and cohabiting couples, reflecting modern family structures. We found that experiencing cancer in a child is not a risk factor f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 11 publications
3
19
0
Order By: Relevance
“…It is difficult to determine the effect of the cancer diagnosis as baseline marriage quality was not assessed. Even so, our results concur with previous studies, which likewise report no impact on divorce rates .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It is difficult to determine the effect of the cancer diagnosis as baseline marriage quality was not assessed. Even so, our results concur with previous studies, which likewise report no impact on divorce rates .…”
Section: Discussionsupporting
confidence: 93%
“…In addition to inclusion of patients with heterogeneous cancers, past studies of the family burden of childhood ALL were in earlier treatment eras or used retrospective data. Studies of childhood cancer's impact on parental marriages yielded conflicting results, with regards to divorce/separation rates . Studies regarding financial burdens likewise showed mixed results though recent studies have utilized prospectively recorded expense‐journals .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a Danish study concluded that childhood cancer did not affect parental separation rates. 23 Collectively, these findings suggest that many parent dyads adapt well to the crisis of having a child with cancer. Indeed, a recent review concluded that childhood cancer does not necessarily affect parent's functioning in terms of emotional closeness, support, and marital satisfaction.…”
Section: Discussionmentioning
confidence: 91%
“…One of the tense incidents is the diagnosis of cancer in one of the family's children. It may cause complications in the adjustment of an adolescent family member such as a sibling of the child with cancer, and has consequences such as less communication with parents, changes in the sibling's relations, feeling jealous of the sick child and being angry with parents (Prchal and Landolt, 2012;Peek and Melnyk, 2010;Grant et al, 2012;Dambi et al, 2015). In such a situation, the adolescent may feel isolated and neglected due to his/her inability to adapt to the situation, being more vulnerable during puberty regarding parents' focus on the needs of the sick family member.…”
Section: Introductionmentioning
confidence: 99%